2019
DOI: 10.1556/063.9.2019.3.44
|View full text |Cite
|
Sign up to set email alerts
|

Teacher burnout in the light of workplace, organizational, and social factors

Abstract: Background and aims We studied teacher burnout and its relationship with job demands and resources, collective self-efficacy, and social support. Previous studies indicate that the factors of burnout (depersonalization, emotional exhaustion, and reduced personal accomplishment) develop in work environment where demands exceed resources, and where social support and collective self-efficacy are both perceived to be low. Methods Online survey method was used (N = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(63 reference statements)
0
2
0
1
Order By: Relevance
“…: a merev tantárgyi követelmények) és leginkább a szociális támogatás mértéke (Heus & Diekstra, 1999). A társas támogatás fontosságát számos más kutatás eredménye is megerősíti (Fiorilli és mtsai, 2019;Russell, Altmaier & Van Velzen, 1987;Sarros & Sarros, 1992), és a magyar tanárok körében is kimagasló szerepe van: azok a tanárok, akik több szociális támogatást éreznek kollégáik részéről, kevésbé vannak kitéve a kiégés veszélyének (Szabó & Jagodics, 2019).…”
Section: Szociokulturális Tényezők Szabályzások a Tanárokra Specifiku...unclassified
“…: a merev tantárgyi követelmények) és leginkább a szociális támogatás mértéke (Heus & Diekstra, 1999). A társas támogatás fontosságát számos más kutatás eredménye is megerősíti (Fiorilli és mtsai, 2019;Russell, Altmaier & Van Velzen, 1987;Sarros & Sarros, 1992), és a magyar tanárok körében is kimagasló szerepe van: azok a tanárok, akik több szociális támogatást éreznek kollégáik részéről, kevésbé vannak kitéve a kiégés veszélyének (Szabó & Jagodics, 2019).…”
Section: Szociokulturális Tényezők Szabályzások a Tanárokra Specifiku...unclassified
“…Finally, many researchers have found that reduced financial provision and the lack of appropriate curricula that could support their work play a key role in the prevalence of the burnout syndrome among S.E. teachers [21][22][23][24].…”
Section: Special Education Teachers' Professional Burnoutmentioning
confidence: 99%
“…Kajian lepas berkaitan burnout dalam kalangan guru menunjukkan dapatan negatif yang boleh menganggu proses pengajaran dan pembelajaran. Szabo & Jagodics (2019) www.msocialsciences.com mendapati guru mengalami tahap burnout sederhana secara keseluruhannya kerana mencatatkan skor sederhana tinggi bagi dimensi keletihan emosi dan tahap sederhana pada dimensi depersonalisasi dan pencapaian peribadi. Kerjaya guru yang terpaksa berhadapan dengan pelbagai ragam pelanggan seperti murid, ibu bapa dan pihak atasan menyebabkan guru rasa terbeban sekali gus mengganggu emosi guru.…”
Section: Pengenalanunclassified